2010
DOI: 10.1124/jpet.110.176743
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondria-Targeted Antioxidant Mitoquinone Protects against Cold Storage Injury of Renal Tubular Cells and Rat Kidneys

Abstract: The majority of kidneys used for transplantation are obtained from deceased donors. These kidneys must undergo cold preservation/storage before transplantation to preserve tissue quality and allow time for recipient selection and transport. However, cold storage (CS) can result in tissue injury, kidney discardment, or long-term renal dysfunction after transplantation. We have previously determined mitochondrial superoxide and other downstream oxidants to be important signaling molecules that contribute to CS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 40 publications
1
72
0
Order By: Relevance
“…Our laboratory previously showed that CS (4 hr) alone induces altered renal mitochondrial function (reduced respiratory complex I-IV activity, using a spectrophotometric assay and isolated renal mitochondria), leading to renal tubular injury [10]. However, it was not clear if mitochondrial damage extended to post-transplant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our laboratory previously showed that CS (4 hr) alone induces altered renal mitochondrial function (reduced respiratory complex I-IV activity, using a spectrophotometric assay and isolated renal mitochondria), leading to renal tubular injury [10]. However, it was not clear if mitochondrial damage extended to post-transplant.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported in isolated rat and pig kidneys that CS alone induced significant renal and mitochondrial injury [10,11]. In this study, we evaluated renal function after 4 hr CS combined with transplantation using a syngeneic transplantation model to minimize confounding effects of the host immune system.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, several in vivo studies in rodents have shown that MitoQ 10 administered orally can protect mitochondria from oxidative damage in a number of models of pathology. These include cardiac ischemia/reperfusion (I/R) injury (Adlam et al 2005;Neuzil et al 2007), damage to endothelial cells in vivo by nitroglycerin (Esplugues et al 2006), hypertension (Graham et al 2009), sepsis (Lowes et al 2008;Supinski, Murphy, and Callahan 2009), adriamycin toxicity (Chandran et al 2009), kidney damage in type I diabetes (Chacko et al 2010), MPTP toxicity in the brain (Ghosh et al 2010), cold preservation of kidney for organ transplantation (Mitchell et al 2011), and cocaine toxicity (Vergeade et al 2010). Other antioxidant moieties such as plastoquinone (Skulachev et al 2009) and the nitroxide TEMPOL (Trnka et al 2008) have also proven to be effective protective agents in vivo (Dikalova et al 2010).…”
Section: Antioxidants Based On Lipophilic Cationsmentioning
confidence: 99%
“…11 Nonspecific antioxidants have proven disappointing as a therapy in AKI, perhaps partly because of the realization that nonmitochondrial ROS have important physiologic signaling roles in the kidney. 12 There has therefore been great interest in the development of antioxidants specifically targeted to the mitochondria; two such agents, mito Q and SkQ1, selectively accumulate in the mitochondrial matrix on account of their positive charge and have shown renoprotective effects in models of cold storage injury 13 and IRI, 14 respectively.…”
mentioning
confidence: 99%